2012
DOI: 10.4202/app.2010.0083
|View full text |Cite
|
Sign up to set email alerts
|

Helodermatid Lizard from the Mio-Pliocene Oak-Hickory Forest of Tennessee, Eastern USA, and a Review of Monstersaurian Osteoderms

Abstract: The extant venomous Gila monster and beaded lizards, species of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…The Gray Fossil Site, located near Gray in Washington County, northeastern Tennessee, eastern United States (36°22′13″ N, 82°29′49″ W; Fig. ), has received close attention in recent years for its abundant well‐preserved animal and plant fossils (Wallace & Wang, ; Hulbert et al, ; Gong et al, ; Liu & Jacques, ; Zobaa et al, ; Mead et al, ; Ochoa et al, ; Worobiec et al, ). The site is interpreted as the fill of a series of paleo‐sinkholes, and is currently exposed on the northern and western faces of a roughly east–west trending hill at Gray (Whitelaw et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The Gray Fossil Site, located near Gray in Washington County, northeastern Tennessee, eastern United States (36°22′13″ N, 82°29′49″ W; Fig. ), has received close attention in recent years for its abundant well‐preserved animal and plant fossils (Wallace & Wang, ; Hulbert et al, ; Gong et al, ; Liu & Jacques, ; Zobaa et al, ; Mead et al, ; Ochoa et al, ; Worobiec et al, ). The site is interpreted as the fill of a series of paleo‐sinkholes, and is currently exposed on the northern and western faces of a roughly east–west trending hill at Gray (Whitelaw et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In order to verify that the morphology of cranial osteoderms can be modeled as a surface tension phenomenon, the quotient between perimeter and the square root of the area of the osteoderms will be used as an indicator. A review of pictures found on national exhibitions, published articles (Lydeker, 1894; Scott, 1903; Bauer and Russell, ; Carpenter, ; Hill, ; Mead et al, ; Arbour and Currie, ; Milinkovitch et al, ) and online (DigiMorph Staff, ; Museum of Comparative Zoology; O'Leary and Kaufman, 2012) was considered (see Table for a full list of the institutions where the studied specimens can be found). As the scales of Nile crocodiles are the result of a process which is not expected to optimize its energy (Milinkovitch et al, ), the scales of a specimen will also be analyzed in order to compare our results with those obtained from a physical cracking process.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, osteoderms covering the cranial bones are thicker, more polygonal in shape, and larger than those from the nuchal region or the rest of the body, which usually are smaller and have a more circular outline. Sometimes, some cranial osteoderms abut others and co‐ossify as a result of their development (Mead et al, ).Osteoderms develop as domed regions of thick collagen within the dermis, first appearing over the ossified head skeleton, then spreading caudally in a process consistent with metaplastic ossification (Moss, ). As the animals mature, the collagen domes increase in size before finally becoming mineralized.…”
Section: Introductionmentioning
confidence: 99%
“…We conditionally assign the osteoderms described herein to Anguidae due to the shape (subrectangular/ovoid for trunk osteoderms, polygonal for cranial osteoderms), and external surficial sculpting patterns (subcircular pits and narrow, irregular grooves) (Mead, Arroyo-Cabrales & Johnson, 1999). Subtle differences in an osteoderm's external surface sculpting is commonly used for taxonomic distinction in fossil and modern anguid lizards (Meszoely & Ford, 1976;Mead, Arroyo-Cabrales & Johnson, 1999;Mead et al, 2012). We refrain from inferring lower-level taxonomic affinities until more complete specimens are recovered from the Fruitland/Kirtland formations; however, we do recognize that there at least two distinct morphotypes of osteoderm within these described specimens.…”
Section: Systematic Paleontologymentioning
confidence: 99%